Shareholder-Manager Conflict and the Information Content of Dividends - Kumar, Praveen (Review of Financial Studies, 1988)
In a model of the firm in which insiders are privately informed of the firm's prospects and investment is endogenous, this article shows the existence of coarse dividend-signaling equilibria: Dividends partition the space of possible prospects of the firm, and changes in dividends reflect "broad", or nonincremental, changes in these prospects. These equilibria are shown to exist under general preference and technology structures, and it is argued that they closely match the following "anomalous" empirical features of corporate dividend payouts: Dividend changes have nontrivial information effects, yet dividends are smoothed (in a world with cyclic prospects), and dividends are poor predictors of future earnings. Furthermore, in performing comparative statics, this article derives cross-sectional and time-series restrictions on the relation of dividend smoothing to observable firm attributes.